Joint Pathologies as a Covert Risk Factor for Rod Fracture after Pedicle Subtraction Osteotomy in Adult Spinal Deformity - Lee, Ki Young; Lee, Jung-Hee; Im, Sang-Kyu (Archives of Clinical and Biomedical Research, 2021)
Background: The recent increase in average life expectancy has increased the prevalence of adult spinal deformity (ASD). Instrumentation failure, including rod fracture (RF), may occur even after successful procedures. RF is the most common cause of revision surgery and pedicle subtraction osteotomy (PSO) is a major risk factor of RF. However, disagreements remain regarding how results are related to hip and knee joint pathologies. Methods: Participants comprised 89 consecutive patients (mean age, 71.2 y) who underwent deformity correction including PSO, with ≥2 years of follow-up. Patients were classified into non-RF (n = 48) and RF groups (n = 41). Radiologic factors including spinopelvic and lower-extremity parameters were measured. Results: Both groups showed severe sagittal imbalance preoperatively. There were no significant differences between groups in patient factors, sagittal and coronal spinopelvic parameters, and osteoarthritis (OA) grade of the joints. However, preoperative structural and functional leg length discrepancy (LLD) and pelvic obliquity significantly differed between groups (P = 0.001, 0.002, and 0.002, respectively). The proportion of knee OA, structural and functional LLD, and knee angular deformity were significantly higher in the RF group than in the non-RF group (P = 0.008, 0.000, 0.020, and 0.012, respectively). Conclusion: Elderly patients with ASD often show degenerative changes in the lower extremities, and even if spine deformity correction is successfully performed, complications, including RF, can occur if joint pathologies are not resolved. Therefore, it is important to consider perioperative treatments for the lower extremities as well as restoration of the spine and pelvis.